1989
DOI: 10.1007/bf00913794
|View full text |Cite
|
Sign up to set email alerts
|

Common problems and coping strategies I: Findings with normal adolescents

Abstract: This study investigated problems commonly experienced by adolescents and the strategies they use to cope with these events. Coping strategies were examined across the subjects' emotional state and their evaluation of the problem. In general, adolescents reported four common stressors that were similar across age groups and gender. However, males differed from females in the frequency of these problems. Further, while the stressors were similar, the frequency with which the coping strategies were employed and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
62
0
7

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(82 citation statements)
references
References 17 publications
13
62
0
7
Order By: Relevance
“…Also, the Kidcope's utility for examining coping strategies reported by various clinical populations has been substantiated. Studies conducted by Spirito and colleagues (Spirito et al, 1990;Stark, Spirito, Williams, and Guevremont, 1989) have yielded preliminary Kidcope norms for the coping of normal populations (age 9-17 years) with common everyday problems. In research involving clinical populations, Spirito, Stark, Williams, Stamoulis, and Axelson (1988b) found significant differences in the reported frequency and perceived efficacy of coping strategies used by chronically ill children and adolescents (ages 10-18 years), referred for psychological evaluation, and a nonreferred chronically ill group.…”
Section: Questionnairesmentioning
confidence: 99%
“…Also, the Kidcope's utility for examining coping strategies reported by various clinical populations has been substantiated. Studies conducted by Spirito and colleagues (Spirito et al, 1990;Stark, Spirito, Williams, and Guevremont, 1989) have yielded preliminary Kidcope norms for the coping of normal populations (age 9-17 years) with common everyday problems. In research involving clinical populations, Spirito, Stark, Williams, Stamoulis, and Axelson (1988b) found significant differences in the reported frequency and perceived efficacy of coping strategies used by chronically ill children and adolescents (ages 10-18 years), referred for psychological evaluation, and a nonreferred chronically ill group.…”
Section: Questionnairesmentioning
confidence: 99%
“…The more ingroup and outgroup acculturation hassles the participants perceived, the more depressive symptoms they reported. These acculturation specific hassles increase the risk of mental health problems among immigrant children and youth in addition to the risk of the general daily hassles related to family, friends, and school, that everybody, independent of immigrant status, may experience (Evan & Poole, 1987;Oppedal & Roysamb, 2004;Stark, Spirito, Willians, & Guevremont, 1989;Seglem, Oppedal, & Roysamb, 2012). Our results support findings from other studies that have shown associations between acculturation risk factors and mental health (Vinokurov, Trickett & Birman, 2002).…”
Section: Depressionmentioning
confidence: 99%
“…In the study, informed consent was necessary, because the participant were required to give out and engage in the frequent interactions in complex manner as supported by Stark et al (2006) who said when participants give their consent to a study, they are empowered rather than the researcher being protected; they are assured of anonymity and confidentiality in order to avoid any possible harm to them. In addition, it sought to avoid deception and harm (Heath et al, 2004).…”
Section: Ethical Issuesmentioning
confidence: 99%